2007
DOI: 10.1021/ol701595n
|View full text |Cite
|
Sign up to set email alerts
|

Indole-Derived Arynes and Their Diels−Alder Reactivity with Furans

Abstract: Arynes derived from any position of the ubiquitous indole nucleus are unknown. We have now provided the first evidence for the formation and trapping of the 4,5-, 5,6-, and 6,7-indolynes. A series of o-dihalo indoles (Cl, Br, F) were synthesized and reacted under metal-halogen exchange conditions to give Diels-Alder cycloadducts in high yield with furan. The use of an excess of tert-butyllithium resulted in the rearrangement of the initially formed cycloadduct; however, employing only a slight excess of n-buty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
18
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 14 publications
3
18
1
1
Order By: Relevance
“…Extremely high levels of regioselectivity are observed experimentally (Table 6), and even azide cycloaddition gives very high selectivity. The 6,7-indolynes also display remarkably high regioselectivity in cycloadditions with 2-substituted furans, unlike 4,5- and 5,6-indolynes 12e. Complementary to our rationalization based on the distortion energies required to achieve the transition state geometry, Buszek and Cramer have also shown that regioselectivity of additions of electron-rich furans to indolynes are influenced by the computed polarization of the C≡C bond 12e.…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations
“…Extremely high levels of regioselectivity are observed experimentally (Table 6), and even azide cycloaddition gives very high selectivity. The 6,7-indolynes also display remarkably high regioselectivity in cycloadditions with 2-substituted furans, unlike 4,5- and 5,6-indolynes 12e. Complementary to our rationalization based on the distortion energies required to achieve the transition state geometry, Buszek and Cramer have also shown that regioselectivity of additions of electron-rich furans to indolynes are influenced by the computed polarization of the C≡C bond 12e.…”
Section: Resultssupporting
confidence: 54%
“…The 6,7-indolynes also display remarkably high regioselectivity in cycloadditions with 2-substituted furans, unlike 4,5- and 5,6-indolynes 12e. Complementary to our rationalization based on the distortion energies required to achieve the transition state geometry, Buszek and Cramer have also shown that regioselectivity of additions of electron-rich furans to indolynes are influenced by the computed polarization of the C≡C bond 12e. This polarization is related to the unsymmetrical bending distortions of the indolyne.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 (Figure 2). We recently discovered the first successful and general route to these reactive intermediates via metal–halogen exchange of o -dihalides 4 and later via fluoride-induced decomposition of o -silyltriflates. 5 We subsequently examined the regioselectivity of indolynes in Diels–Alder reactions with 2-substituted furans.…”
mentioning
confidence: 99%